Development of the functional model to control the levels of electricity consumption by underground ironore enterprises - Sinchuk, Oleg; Sinchuk, Ihor; Kozakevych, Ihor; Fedotov, Vladislav; Serebrenikov, Vadim; Lokhman, Natalya; Beridze, Tatiana; Boiko, Serhii; Pyrozhenko, Andrey; Yalova Аlena (Eastern-European Journal of Enterprise Technologies, 2018)
This paper reports results of the study into assessing the features and devising a tactic for the development of structures for the systems that control levels of electricity consumption by receivers at iron-mining enterprises employing the underground technique for extracting iron ore raw materials (IOR). It is shown that the advantages of the proposed structure, compared with existing variants, is the implementation within its functional of control solutions that are predefined by the specificity in the operational technology of electric energy (EE) receivers at these types of enterprises. The solution became possible based on the unification of the electrical energy complex of these enterprises into a single structure: electricity supply systems ‒ EE receivers. A list of consumers has been compiled, which form a shape of daily timetables of electrical loads at an iron ore enterprise ‒ the so-called stationary installations that consume more than 80 % of the total consumption of EE. It is these consumers that were included in the category of EE receivers‒regulators. Individual optimization of operational modes of the work of these receivers over a day’s underlies the logic of control over the levels of EE consumption. Such a structure of optimization appears appropriate based on the fact that a price for the EE consumed by an enterprise over 24 hours is formed by the energy-generating organization differentiated in a function of zonal tariffs: peak, half-peak, night. Upon determining a dependence of energy consumption levels by the receivers-regulators on controlling and perturbing variables, it has been established, and recommended for implementation, to control the level of EE consumption based on the substantiated and predefined criteria, whose essence comes down to the minimization of this indicator. The present work has synthesized a mathematical model, based on which the algorithm of control was designed. This makes it possible to not only minimize the level of power consumption by taking into consideration the zonal tariff prices for the EE consumed, but to control flows in the cases of possible limitations for the levels of electricity supply by the side that supplies power to an energy system.